Characterizing Creative Teachers and Students - Oledan, Alexis Michael; Limjap, Auxencia A. (Asia Research Network Journal of Education, 2024)
Creativity is an essential 21st-century skill that students must cultivate across all subjects, including mathematics. While mathematical creativity lacks a universal definition, there is broad consensus among researchers on its importance for students to appreciate the underlying techniques and concepts of mathematics. However, teachers often face challenges in designing activities that effectively promote this creativity. This study investigates the roles of teachers participating in lesson study and students engaging in enhancement classes to explore how creative qualities can be fostered. Employing a single case study approach, the research incorporated open-ended mathematical tasks within research lessons to examine creativity as a personal trait. Data were collected from various sources, including portfolios, video recordings, one-on-one interviews, and session logs, focusing on the planning, implementation, and reflection stages involving both teachers and students. The findings highlight key characteristics of creative teachers and students. For teachers, three primary themes emerged: the quality and effectiveness of teaching strategies, open-mindedness, and flexibility, alongside other divergent thinking skills. For students, the critical themes identified were mental ability and divergent thinking, open-mindedness, and resourcefulness. Overall, the study underscores the importance of fostering these creative qualities in both teachers and students to enhance mathematical creativity and improve the educational experience.